Evaluation and management of voice disorders: Our experiences - Thakur, Rishikesh; Jha, Abishesh; Thakur, Sanjeev Kumar (Asian Journal of Medical Sciences, 2022)
Background: Change in voice is one of the most common complains among patients visiting to ENT outpatient. The causes are numerous and need to be evaluated before approaching to curative intent of treatment. Aims and Objectives: The current study was designed with an aim to analyze the spectrum of voice disorders and their management option. Materials and Methods: Prospective study conducted between June 25, 2020, and November 30, 2021. Clinical, demographic profiles were recorded. Fiber-optic laryngoscopy was performed in all the cases. Radiology examination computed tomography/magnetic resonance imaging was supplemented only in required cases. Treatment was executed based of etiological profile analysis. Minimum 3 months follow-up was collected post-therapy. Statistical analysis was performed using Statistical Package for the Social Sciences version 24. Pearson Chi-square test was used for see the association between parameters. P-value was considered significant while being <0.05. Results: Out of 218 patients, the most patients (approx. 70%) occupied in the age group of 30–50 years. There was male predominance (76.6%). Voice change secondary to laryngopharyngeal reflux was seen in 56.4% of cases. Benign vocal fold lesions (nodule/cyst/polyp) were noticed in 26.5% of cases. Malignant lesions were seen in 1.8% of cases. Benign vocal fold lesions (polyp and cyst) were treated by microlaryngeal surgery (MLS). Pre-malignant lesion (leukoplakia) was treated with MLS stripping. Out of four malignant lesions, one was in early stage and underwent supraglottic laryngectomy while others were in advanced stage (T4) and treated by total laryngectomy. Conclusions: Voice disorders comprise wide etiological profile from reflux to malignant lesion. Timely proper evaluation followed by definitive management achieves good treatment outcomes.